Writing Captivity in the Early Modern Atlantic : Circulations of Knowledge and Authority in the Iberian and English Imperial Worlds - Voigt, Lisa (Associate professor) (Book collections on Project MUSE., 2009)
Drawing on texts written by and about European and Euro-American captives in a variety of languages and genres, this book explores the role of captivity in the production of knowledge, identity, and authority in the early modern imperial world. The practice of captivity attests to the violence that infused relations between peoples of different faiths and cultures in an age of extraordinary religious divisiveness and imperial ambitions.